A Fully Implantable and Programmable Epidural Spinal Cord Stimulation System for Rats With Spinal Cord Injury - Guangwei Mao; Zhijun Zhou; Hao Su; Yaozhong Chen; Jianjun Zhang; Chiyuan Zhang; Zhigong Wang; Xiaoying Lu (IEEE, 2023)
Epidural spinal cord stimulation (ESCS) is a potential treatment for the recovery of the motor function in spinal cord injury (SCI) patients. Since the mechanism of ESCS remains unclear, it is necessary to study the neurophysiological principles in animal experiments and standardize the clinical treatment. In this paper, an ESCS system is proposed for animal experimental study. The proposed system provides a fully implantable and programmable stimulating system for complete SCI rat model, along with a wireless charging power solution. The system is composed of an implantable pulse generator (IPG), a stimulating electrode, an external charging module and an Android application (APP) via a smartphone. The IPG has an area of ${25} × {25}$ mm2 and can output 8 channels of stimulating currents. Stimulating parameters, including amplitude, frequency, pulse width and sequence, can be programmed through the APP. The IPG was encapsulated with a zirconia ceramic shell and two-month implantable experiments were carried out in 5 rats with SCI. The main focus of the animal experiment was to show that the ESCS system could work stably in SCI rats. The IPG implanted in vivo can be charged through the external charging module in vitro without anesthetizing the rats. The stimulating electrode was implanted according to the distribution of ESCS motor function regions of rats and fixed on the vertebrae. The lower limb muscles of SCI rats can be activated effectively. The two-month SCI rats needed greater stimulating current intensity than the one-month SCI rats The results indicated that the stimulating system provides an effective and simplified tool for studying the ESCS application in motor function recovery for untethered animals.